Gas barrier film

By optimizing the hardness and surface roughness ratio of the inorganic oxide layer in the gas barrier film and forming a transparent conductive layer in an appropriate position, the shortcomings of the existing gas barrier film in terms of gas barrier properties are solved, and better gas barriers are achieved and conductivity.

CN119431858APending Publication Date: 2025-02-14OIKE & CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410655796.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-04
Filing Date
2024-05-24
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

There is room for improvement in the existing gas barrier films in terms of gas barrier properties, especially the relationship between hardness and surface roughness has not been fully optimized.

Method used

The gas barrier of the gas barrier film is improved by appropriately adjusting the ratio of hardness to surface roughness (H/Ra ≥ 0.7 or E/Ra ≥ 3.4) on the inorganic oxide layer of the gas barrier film and forming a transparent conductive layer in an appropriate position. and conductivity.

Benefits of technology

Excellent gas barrier properties and conductivity of the gas barrier film are achieved, and the overall performance of the film is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004857805930000091
    Figure BDA0004857805930000091
  • Figure BDA0004857805930000101
    Figure BDA0004857805930000101
  • Figure BDA0004857805930000121
    Figure BDA0004857805930000121
Patent Text Reader

Abstract

Provided is a gas barrier film exhibiting excellent gas barrier properties. The gas barrier film is provided with a substrate, a hard coat layer, and an inorganic oxide layer in this order, the inorganic oxide layer contains a silicon oxide, and the ratio (H / Ra) of the indentation hardness H measured from the surface of the inorganic oxide layer by a nanoindentation method to the surface roughness Ra of the hard coat layer is 0.7 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a gas barrier film. More specifically, the present invention relates to a gas barrier film having excellent gas barrier properties. Background Art

[0002] Conventionally, gas barrier films based on plastic films have been used as packaging materials for food and medical products, display devices, solar cells and other electronic device components. In order to block gases such as oxygen and water vapor, the gas barrier film has a gas barrier layer composed of a metal or a metal oxide.

[0003] Patent Document 1 discloses a gas barrier film including silicon and oxygen and having a gas barrier layer with a predetermined hardness.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2011-143551 Summary of the invention

[0007] Problems to be solved by the invention

[0008] However, the gas barrier film described in Patent Document 1 has room for improvement.

[0009] The present invention has been made in view of such conventional inventions, and an object of the present invention is to provide a gas barrier film exhibiting excellent gas barrier properties.

[0010] Technical solutions to solve problems

[0011] The inventors of the present invention have conducted intensive research and found that by focusing on the relationship between the hardness and surface roughness of the gas barrier layer and optimizing them, better gas barrier properties can be obtained, thereby completing the present invention. That is, the gas barrier film of the present invention that solves the above-mentioned problems mainly includes the following configurations.

[0012] (1) A gas barrier film comprising, in order, a substrate, a hard coating layer, and an inorganic oxide layer, wherein the inorganic oxide layer comprises silicon oxide, and the ratio (H / Ra) of the indentation hardness H measured from the surface of the inorganic oxide layer by a nanoindentation method to the surface roughness Ra of the hard coating layer is 0.7 or more.

[0013] According to such a configuration, the gas barrier film exhibits excellent gas barrier properties.

[0014] (2) A gas barrier film comprising, in order, a substrate, a hard coating layer and an inorganic oxide layer, wherein the inorganic oxide layer contains silicon oxide, and the ratio (E / Ra) of the indentation elastic modulus E measured from the surface of the inorganic oxide layer by a nanoindentation method to the surface roughness Ra of the hard coating layer is 3.4 or more.

[0015] According to such a configuration, the gas barrier film exhibits excellent gas barrier properties.

[0016] (3) A gas barrier film comprising, in sequence, a substrate, a hard coating layer and an inorganic oxide layer, wherein the inorganic oxide layer comprises silicon oxide, and the indentation hardness measured from the surface of the inorganic oxide layer by a nanoindentation method is greater than 0.55 GPa, and the indentation elastic modulus is greater than 5.30 GPa, and the surface roughness Ra of the hard coating layer is less than 2.3 nm.

[0017] According to such a configuration, the gas barrier film exhibits excellent gas barrier properties.

[0018] (4) The gas barrier film according to any one of (1) to (3), wherein the inorganic oxide layer has a transparent conductive layer on a surface opposite to the hard coat layer, and the transparent conductive layer contains indium tin oxide.

[0019] According to such a configuration, the gas barrier film exhibits excellent gas barrier properties and electrical conductivity.

[0020] (5) The gas barrier film according to (4), wherein an indentation hardness measured from a surface of the transparent conductive layer by a nanoindentation method is 0.80 GPa or more.

[0021] According to such a configuration, the gas barrier film exhibits excellent gas barrier properties and electrical conductivity.

[0022] (6) The gas barrier film according to any one of (1) to (3), wherein the substrate has a transparent conductive layer on a surface opposite to the hard coat layer, and the transparent conductive layer contains indium tin oxide.

[0023] According to such a configuration, the gas barrier film exhibits excellent gas barrier properties and electrical conductivity.

[0024] Effects of the Invention

[0025] According to the present invention, a gas barrier film having excellent gas barrier properties can be provided. DETAILED DESCRIPTION

[0026] Gas barrier film

[0027] First embodiment

[0028] A gas barrier film according to one embodiment of the present invention comprises a substrate, a hard coating layer and an inorganic oxide layer in sequence. The inorganic oxide layer comprises silicon oxide. The ratio (H / Ra) of the indentation hardness H measured from the surface of the inorganic oxide layer by the nanoindentation method to the surface roughness Ra of the hard coating layer is 0.7 or more. The following describes each structure.

[0029] Substrate

[0030] The substrate can use a resin film commonly used in gas barrier films. If an example is given, the substrate is a plastic film or plastic sheet such as polyethylene terephthalate (PET), cycloolefin polymer (COP), polyethylene (PE), polyimide (PI), polyethylene naphthalate (PEN), polycarbonate (PC), triacetyl cellulose (TAC), etc. In addition, for example, it can also be a flame retardant substrate to which flame retardancy is imparted to polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polycarbonate (PC), etc. Among them, the substrate is preferably composed of a flexible (soft) material such as a plastic film. Thus, the gas barrier film can be preferably widely used in electronic device components such as displays or solar panels, etc.

[0031] The thickness of the substrate is not particularly limited. As an example, the thickness of the substrate is preferably 12 μm or more, more preferably 25 μm or more. In addition, the thickness of the substrate is preferably 200 μm or less, more preferably 125 μm or less. When the thickness of the substrate is within the above range, the obtained gas barrier film can show appropriate rigidity and strength.

[0032] Hard coating

[0033] The hard coat layer is arranged on the substrate. The resin material constituting the hard coat layer is not particularly limited. If an example is given, the resin material constituting the hard coat layer is a polyester resin, an acrylic resin, a polyurethane resin, a thermosetting resin consisting of an epoxy resin, and a light-curing resin (acrylic resin, epoxy resin) etc. Wherein, from the viewpoint of a hard coat layer having a short curing time and excellent properties, the resin material constituting the hard coat layer is preferably a light-curing resin, more preferably a urethane acrylate.

[0034] The method for forming the hard coat layer is not particularly limited. As an example, the hard coat layer can be formed on the substrate by gravure coating, reverse coating, nano coating, bar coating, die coating, dipping, screen printing, or the like.

[0035] The thickness of the hard coating layer is not particularly limited. The thickness of the hard coating layer is preferably 0.5 μm or more, and more preferably 1.0 μm or more. In addition, the thickness of the hard coating layer is preferably 20 μm or less, and more preferably 10 μm or less. When the thickness of the hard coating layer is within the above range, the gas barrier film can easily be given sufficient surface hardness.

[0036] Inorganic oxide layer

[0037] The inorganic oxide layer is a layer including silicon oxide provided on the hard coating layer.

[0038] Silicon oxide is a silicon oxide represented by a composition formula SiOx (0<x≤2, preferably 1≤x<2). The x of SiOx may be an inclined film having an inclination in the thickness direction of the inorganic oxide layer or may be a uniform film.

[0039] The content of silicon oxide in the compound constituting the inorganic oxide layer is preferably 95% by mass or more, more preferably 98% by mass or more, and further preferably 99% by mass or more. It should be noted that in the present embodiment, the inorganic oxide layer may also contain impurities that are inevitably included. When the content of silicon oxide is within the above range, the gas barrier film can exhibit excellent gas barrier properties.

[0040] The thickness of the inorganic oxide layer is not particularly limited. As an example, the thickness of the inorganic oxide layer is preferably 20 nm or more, more preferably 100 nm or more. In addition, the thickness of the inorganic oxide layer is preferably 1000 nm or less, more preferably 500 nm or less. When the thickness of the inorganic oxide layer is within the above range, the obtained gas barrier film exhibits excellent gas barrier properties.

[0041] The method for forming the inorganic oxide layer is not particularly limited. If an example is given, the inorganic oxide layer can be formed by sputtering, can be formed by a wet coating method, or can be formed by a combination of sputtering and wet coating methods. In the case of formation by sputtering, specifically, the inorganic oxide layer can be formed on a substrate by a reactive sputtering method in a mixed gas atmosphere of argon and oxygen using a target composed of silicon. In the case of formation by wet coating, specifically, the inorganic oxide layer can be formed by coating polysilazane (PHPS) on a substrate by a known wet coating method and converting it into silicon oxide.

[0042] The ratio (H / Ra) of the indentation hardness H measured from the surface of the inorganic oxide layer by the nanoindentation method to the surface roughness Ra of the hard coating layer is 0.7 or more, preferably 0.8 or more, more preferably 1.0 or more, and further preferably 2.0 or more. The ratio (H / Ra) is preferably 4.0 or less, more preferably 3.7 or less. When the ratio (H / Ra) is less than 0.7, the gas barrier property of the gas barrier film is poor. It should be noted that in the specification of this application, when discussing the value of the ratio (H / Ra), the value calculated by setting the unit of H to GPa and the unit of Ra to nm is used. In addition, the "nanoindentation method" is a method of pressing a special diamond indenter into the surface of the sample to measure the load (indentation strength) and displacement (indentation depth). The indentation hardness H can be measured using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.), with the test load set to 0.1mN, and under the condition of an indentation depth of less than 10% of the film thickness of the outermost layer of the layer to be measured. The surface roughness Ra can be measured using a white light interference microscope (NT-9100, manufactured by Veeco) with a 5x objective lens and Phase-Shift Interferometry mode.

[0043] Transparent conductive layer

[0044] The transparent conductive layer can preferably be formed on the surface of the inorganic oxide layer on the opposite side of the hard coating layer. In addition, the transparent conductive layer can preferably be formed on the surface of the substrate on the opposite side of the hard coating layer. The material contained in the transparent conductive layer is not particularly limited as long as it is a transparent conductive material showing transparency and conductivity. If an example is given, it is a metal oxide of a metal such as indium, tin, zinc, gallium, antimony, titanium, silicon, zirconium, magnesium, aluminum, gold, silver, copper, palladium, tungsten, etc. Among them, the transparent conductive layer preferably includes indium tin oxide (ITO), aluminum oxide, indium zinc oxide (IZO), aluminum-added zinc oxide (AZO), gallium-added zinc oxide (GZO), indium cerium oxide (ICO), etc., and particularly preferably includes ITO. The transparent conductive material contained in the transparent conductive layer can be composed of one of these materials or a plurality of them. The transparent conductive material contained in the transparent conductive layer is preferably 95% by mass or more in the compound constituting the transparent conductive layer, more preferably 98% by mass or more, and further preferably 99% by mass or more. In addition, in the present embodiment, the transparent conductive layer may contain impurities that are inevitably contained. By providing such a transparent conductive layer, the gas barrier film has excellent gas barrier properties and electrical conductivity.

[0045] The thickness of the transparent conductive layer is not particularly limited. As an example, the thickness of the transparent conductive layer is preferably 13 nm or more, more preferably 15 nm or more. In addition, the thickness of the transparent conductive layer is preferably 500 nm or less, more preferably 300 nm or less. When the thickness of the transparent conductive layer is within the above range, the gas barrier film can obtain excellent conductivity and transparency.

[0046] The indentation hardness measured from the surface of the transparent conductive layer by the nanoindentation method is preferably 0.80 GPa or more, more preferably 1.00 GPa or more, further preferably 2.00 GPa or more, and particularly preferably 2.60 GPa or more. Thus, the gas barrier property of the gas barrier film is more excellent. The indentation hardness can be measured using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.), with the test load set to 0.1 mN, and under the condition of an indentation depth of less than 10% of the film thickness of the outermost layer of the layer to be measured.

[0047] The method for forming the transparent conductive layer is not particularly limited. If an example is given, the transparent conductive layer can be formed on the inorganic oxide layer or substrate by a dry coating method such as vacuum evaporation, sputtering, ion plating, or a wet coating method (coating method), etc., using a composition constituting the transparent conductive layer. Among them, from the reason that the film formation of the thin film is easy, the transparent conductive layer is preferably formed by a dry coating method, preferably by a magnetron sputtering method, by reactive sputtering using a metal oxide target (ITO). At this time, for example, oxygen, nitrogen, water vapor, etc. can also be introduced, or ozone addition, plasma irradiation, ion assistance, etc. can be used in combination.

[0048] As described above, according to the present embodiment, the gas barrier film exhibits excellent gas barrier properties.

[0049] Second embodiment

[0050] A gas barrier film according to an embodiment of the present invention comprises a substrate, a hard coating layer and an inorganic oxide layer in sequence. The inorganic oxide layer comprises silicon oxide. The ratio (E / Ra) of the indentation elastic modulus E measured from the surface of the inorganic oxide layer by nanoindentation to the surface roughness Ra of the hard coating layer is 3.4 or more. Below, each composition is described. It should be noted that in the following description, each layer is the same as the above-mentioned layers in the first embodiment, so the description is appropriately omitted.

[0051] In the gas barrier film of the present embodiment, the ratio (E / Ra) of the indentation elastic modulus E measured from the surface of the inorganic oxide layer by the nanoindentation method to the surface roughness Ra of the hard coating layer is only 3.4 or more, preferably 4.5 or more, more preferably 5.8 or more, and further preferably 8.3 or more. The ratio (E / Ra) is preferably 20.0 or less, more preferably 19.0 or less. When the ratio (E / Ra) is less than 3.4, the gas barrier property of the gas barrier film is poor. It should be noted that in the specification of this application, when discussing the value of the ratio (E / Ra), the value calculated by setting the unit of E to GPa and the unit of Ra to nm is used. In addition, the indentation elastic modulus E can be measured using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.), setting the test load to 0.1 mN, and under the condition of an indentation depth of less than 10% of the film thickness of the outermost layer of the layer to be measured.

[0052] The gas barrier film of the present embodiment may also be provided with a transparent conductive layer similar to the gas barrier film described above in the first embodiment.

[0053] As described above, the gas barrier film of the present embodiment exhibits excellent gas barrier properties.

[0054] Third embodiment

[0055] A gas barrier film according to an embodiment of the present invention comprises a substrate, a hard coating layer and an inorganic oxide layer in sequence. The inorganic oxide layer comprises silicon oxide. The indentation hardness measured from the surface of the inorganic oxide layer by nanoindentation is 0.55 GPa or more, and the indentation elastic modulus is 5.30 GPa or more. The surface roughness Ra of the hard coating layer is 2.3 nm or less. Below, each structure is described. It should be noted that in the following description, each layer is the same as the above-mentioned layers in the first embodiment, so the description is appropriately omitted.

[0056] In the gas barrier film of the present embodiment, the indentation hardness measured from the surface of the inorganic oxide layer by the nanoindentation method is only required to be 0.55 GPa or more, preferably 0.79 GPa or more, more preferably 1.37 GPa or more, and further preferably 1.90 GPa or more. In addition, the indentation hardness is preferably 3.00 GPa or less, more preferably 2.60 GPa or less. When the indentation hardness is less than 0.55 GPa, the gas barrier property of the gas barrier film is poor. It should be noted that the indentation hardness can be measured using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.), with the test load set to 0.1 mN, under the condition of an indentation depth of less than 10% of the film thickness of the outermost layer of the layer to be measured.

[0057] In the gas barrier film of the present embodiment, the indentation elastic modulus measured from the surface of the inorganic oxide layer by the nanoindentation method is only required to be 5.30 GPa or more, preferably 5.80 GPa or more, more preferably 7.80 GPa or more, and further preferably 10.20 GPa or more. In addition, the indentation elastic modulus is preferably 15.00 GPa or less, more preferably 13.00 GPa or less. By having the indentation elastic modulus within the above range, the gas barrier film has excellent gas barrier properties. It should be noted that the indentation elastic modulus can be measured using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.), with the test load set to 0.1 mN, and under the condition of an indentation depth of less than 10% of the film thickness of the outermost layer of the layer to be measured.

[0058] In the gas barrier film of the present embodiment, the surface roughness Ra of the hard coating layer is as long as it is less than 2.3nm, preferably less than 2.0nm, and more preferably less than 1.4nm. In addition, the surface roughness Ra is preferably greater than 0.1nm, and more preferably greater than 0.5nm. When the surface roughness is greater than 2.3nm, the gas barrier property of the gas barrier film is poor. It should be noted that the surface roughness Ra can be measured using a white light interference microscope (NT-9100, manufactured by Veeco) using a 5x objective lens and Phase-Shift Interferometry mode.

[0059] The gas barrier film of the present embodiment may also be provided with a transparent conductive layer similar to the gas barrier film described above in the first embodiment.

[0060] As described above, the gas barrier film of the present embodiment exhibits excellent gas barrier properties.

[0061] Example

[0062] The present invention will be described in more detail below by way of examples. The present invention is not limited to these examples. In addition, "%" means "mass %" unless otherwise specified.

[0063] Example 1

[0064] A PET film (thickness: 50 μm) was used as a substrate, and a hard coating layer (HC) composed of coating material 1 (UV-1700B, manufactured by Mitsubishi Chemical Corporation) was applied on the substrate by a bar coater, and then dried at 80° C. for 1 minute and heated at 300 mJ / cm in a nitrogen atmosphere. 2 The hard coating layer was formed by UV curing under the conditions of . The thickness of the obtained hard coating layer was 1.5 μm. Next, an inorganic oxide layer (thickness 25 nm) of SiOx was formed on the hard coating layer by reactive sputtering based on the magnetron sputtering method using a Si target to obtain a gas barrier film.

[0065] Example 2

[0066] A PET film (thickness: 50 μm) was used as a substrate, and a hard coating layer (HC) composed of coating material 2 (Z-773-ML, manufactured by Aica Industries, Ltd.) was applied on the substrate by a bar coater, and then dried at 80°C for 1 minute and heated at 300 mJ / cm in a nitrogen atmosphere. 2 The obtained hard coating layer is formed by UV curing under the conditions of. The thickness of the obtained hard coating layer is 1.5μm. Next, an inorganic oxide layer is formed on the hard coating layer by the following method. First, PHPS (polysilazane) is applied on the hard coating layer by a wet process (rod coater), dried at 140°C for 1 minute, and allowed to stand at 25°C for 2 weeks to form silicon oxide. The thickness of the obtained SiOx (PHPS conversion layer) is 160nm. Next, SiOx with a thickness of 25nm is formed on the SiOx (PHPS conversion layer) by reactive sputtering based on the magnetron sputtering method using a Si target to obtain a gas barrier film.

[0067] Example 3

[0068] A gas barrier film was produced by the same method as in Example 2 except that the coating material of the hard coat layer was changed to coating material 1 (UV-1700B, manufactured by Mitsubishi Chemical Corporation).

[0069] Example 4

[0070] A gas barrier film was produced by the same method as in Example 2 except that the coating material of the hard coat layer was changed to coating material 3 (UV-7630B, manufactured by Mitsubishi Chemical Corporation).

[0071] Example 5

[0072] A gas barrier film was produced in the same manner as in Example 2 except that the coating material of the hard coat layer was changed to coating material 4 (A-DCP, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.).

[0073] Example 6

[0074] A gas barrier film was produced by the same method as in Example 2 except that the coating material of the hard coat layer was changed to coating material 5 (A-DPH, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.).

[0075] Comparative Example 1

[0076] A gas barrier film was produced by the same method as in Example 1 except that the coating material of the hard coat layer was changed to coating material 6 (UV-7610B, manufactured by Mitsubishi Chemical Corporation).

[0077] Comparative Example 2

[0078] A gas barrier film was produced by the same method as in Example 2 except that the coating material of the hard coat layer was changed to coating material 6 (UV-7610B, manufactured by Mitsubishi Chemical Corporation).

[0079] Comparative Example 3

[0080] A gas barrier film was produced by the same method as in Example 1 except that the coating material of the hard coat layer was changed to coating material 2 (Z-773-ML, manufactured by Aica Industries, Ltd.).

[0081] Comparative Example 4

[0082] A gas barrier film was produced by the same method as in Example 1 except that the coating material of the hard coat layer was changed to coating material 3 (UV-7630B, manufactured by Mitsubishi Chemical Corporation).

[0083] Comparative Example 5

[0084] A gas barrier film was produced in the same manner as in Example 1 except that the coating material of the hard coat layer was changed to coating material 4 (A-DCP, manufactured by Shin-Nakamura Chemical Industry Co., Ltd.).

[0085] Example 7

[0086] A transparent conductive layer was formed by reactive sputtering using an ITO target (SnO2: 10 mass %) on the inorganic oxide layer of the gas barrier film produced in Example 1. The thickness of the ITO transparent conductive layer was 18 nm.

[0087] Examples 8 to 12, Comparative Examples 6 to 10

[0088] In Example 8, a transparent conductive layer is formed on the inorganic oxide layer of the gas barrier film prepared in Example 2, in Example 9, in Example 3, in Example 10, in Example 4, in Example 11, in Example 5, in Example 12, in Comparative Example 6, in Comparative Example 1, in Comparative Example 7, in Comparative Example 2, in Comparative Example 8, in Comparative Example 3, in Comparative Example 9, in Comparative Example 4, and in Comparative Example 10 in the same manner as in Example 7.

[0089] [Table 1]

[0090]

[0091] [Table 2]

[0092]

[0093] Adhesion (cross-cut peel test), surface roughness, indentation hardness, indentation elastic modulus, thermal expansion coefficient, and water vapor transmission rate (WVTR) were measured by the following evaluation methods. The results are shown in Tables 1 to 3.

[0094] Adhesion (checkerboard peel test)

[0095] 11 cuts were made on the test surface at equal intervals (1.5 mm), and the direction was changed by 90°. 11 cuts were made at equal intervals (1.5 mm) to make 100 checkerboards with 10×10 vertical and horizontal grids. A transparent tape (manufactured by NICHIBAN Co., Ltd., model: CT405AP-18) was pasted on it, attached to the test surface, and left to stand for 1 minute. Then, holding one end of the tape, the tape was instantly peeled off in a direction perpendicular to the laminated surface, and the number of checkerboards that were not peeled off and remained was investigated.

[0096] Surface roughness

[0097] The surface roughness (Ra, Rz, Rt) was measured using a white light interference microscope (NT-9100, manufactured by Veeco Corporation) under the measurement conditions of a 5x objective lens and Phase-Shift Interferometry mode.

[0098] Indentation hardness

[0099] The measurement was performed using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.) under a test load of 0.1 mN. The indentation depth was set to 2.5 nm or less when measured from the surface of the inorganic oxide layer and to 1.8 nm or less when measured from the surface of the transparent conductive layer.

[0100] Indentation elastic modulus

[0101] The measurement was performed using a nanoindentation tester (ENT-2100, manufactured by Elionix Co., Ltd.) under a test load of 0.1 mN. The indentation depth was set to 2.5 nm or less when measured from the surface of the inorganic oxide layer and to 1.8 nm or less when measured from the surface of the transparent conductive layer.

[0102] Coefficient of thermal expansion

[0103] The value is calculated by sandwiching a 70 mm square measurement sample with transparent glass plates and measuring the size of the measurement sample at each temperature. The size measurement of the measurement sample is performed using an image dimension meter (IM6010, manufactured by Keyence Corporation).

[0104] Water Vapor Transmission Rate (WVTR)

[0105] The water vapor transmission rate (%) was measured using DELTAPERM (DP-UH2AT, manufactured by Technolox) in accordance with the “differential pressure method (ISO 15106-5)”.

[0106] [Table 3]

[0107]

[0108] As shown in Tables 1 to 3, the gas barrier film of the present invention has a small water vapor permeability and is excellent in gas barrier properties.

Claims

1. A gas barrier film comprising, in order, a substrate, a hard coating layer and an inorganic oxide layer, The inorganic oxide layer comprises silicon oxide, The ratio of the indentation hardness H measured from the surface of the inorganic oxide layer by a nanoindentation method to the surface roughness Ra of the hard coating layer, that is, H / Ra, is 0.7 or more.

2. A gas barrier film comprising, in order, a substrate, a hard coating layer and an inorganic oxide layer, The inorganic oxide layer comprises silicon oxide, The ratio of the indentation elastic modulus E measured from the surface of the inorganic oxide layer by a nanoindentation method to the surface roughness Ra of the hard coating layer, namely, E / Ra, is 3.4 or more.

3. A gas barrier film comprising, in order, a substrate, a hard coating layer and an inorganic oxide layer, The inorganic oxide layer comprises silicon oxide, The indentation hardness measured from the surface of the inorganic oxide layer by a nanoindentation method is 0.55 GPa or more, and the indentation elastic modulus is 5.30 GPa or more, The surface roughness Ra of the hard coating layer is 2.3 nm or less.

4. The gas barrier film according to any one of claims 1 to 3, wherein A transparent conductive layer is provided on the surface of the inorganic oxide layer opposite to the hard coating layer, The transparent conductive layer includes indium tin oxide.

5. The gas barrier film according to claim 4, wherein The indentation hardness measured from the surface of the transparent conductive layer by a nanoindentation method is 0.80 GPa or more.

6. The gas barrier film according to any one of claims 1 to 3, wherein A transparent conductive layer is provided on the surface of the substrate opposite to the hard coating layer. The transparent conductive layer includes indium tin oxide.

Citation Information

Patent Citations

  • Gas barrier film, method of manufacturing the same and organic photoelectric conversion element

    JP2011143551A